2009
DOI: 10.4049/jimmunol.0803591
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Polyelectrolyte Microcapsules: Antigen Delivery Tools with Th17 Skewing Activity after Pulmonary Delivery

Abstract: Because of their large surface area, the lungs appear an attractive route for noninvasive vaccine delivery, harboring the potential to induce local mucosal immune responses in addition to systemic immunity. To evoke adaptive immunity, Ags require the addition of adjuvants that not only enhance the strength of the immune response but also determine the type of response elicited. In this study, we evaluate the adjuvant characteristics of polyelectrolyte microcapsules (PEMs) consisting of the biopolymers dextran-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 51 publications
2
83
0
2
Order By: Relevance
“…15,16 As an example, our group encapsulated antigen proteins in polyelectrolyte microcapsules consisting of dextran sulfate and poly-L-arginine; we showed that such capsules degrade in dendritic cells through proteases and subsequently release the antigen. 3,17 Besides tuning the permeability of the capsule shell by variations in shell thickness, the capsule surface can also be functionalized by e.g. poly(ethylene glycol), 18 lipids, 19 antibodies, 20 dyes 21 and nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 As an example, our group encapsulated antigen proteins in polyelectrolyte microcapsules consisting of dextran sulfate and poly-L-arginine; we showed that such capsules degrade in dendritic cells through proteases and subsequently release the antigen. 3,17 Besides tuning the permeability of the capsule shell by variations in shell thickness, the capsule surface can also be functionalized by e.g. poly(ethylene glycol), 18 lipids, 19 antibodies, 20 dyes 21 and nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their relatively big size, LbL capsules are readily internalized not only by professional phagocytes (DCs [25,72,73] and macrophages [74] largely reduced by cytochalasin D, indicating particle internalization involves an actin dependent process. Furthermore, particle uptake was reduced by incubation with rottlerin, suggesting macropinocytosis as the predominant route of uptake in DCs.…”
Section: In Vitro Behaviour Of Lbl Capsules and Their Cargomentioning
confidence: 99%
“…So far the following biotherapeutics have been encapsulated in CaCO 3 templated PMLC: dextran, a-lactalbumin, lysosyme, horseradish peroxidise, glucose oxidase, catalase, ovalbumin, bovie serum albumin, achymotrypsin, insulin DNA and pronase. [15,17,18,[24][25][26][27][28] A third category of template particles that have gathered considerable attention in literature are hydrogel beads. Hydrogels are strongly hydrated 3D networks which, due to their aqueous environment offer good preservation of the biotherapeutics' bioactivity upon encapsulation.…”
Section: Pre-loaded Templatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The most widespread and best understood pair of polymers is the system of poly(styrene sulfonate) (PSS) and poly(allyamine hydrochloride) (PAH). However, there are many other polymers in use and it is also possible to produce biodegradable capsules made of polymers that can be digested/metabolized inside living cells, for example by proteases present in the lysosome [7,8]. There are two ways to load the capsules, the coprecipitation method, where the cargo is entrapped in the template and remains inside the capsules after removal of the template material, and the postloading method, where the permeability of the capsules can be controlled externally by variation of pH, salt concentration or temperature [9], and the cargo can be loaded into the empty capsules after the synthesis [10].…”
Section: Polyelectrolyte Multilayer Capsulesmentioning
confidence: 99%